Compact models and measurement techniques for high-speed interconnects - Sharma, Rohit (SpringerBriefs in Electrical and Computer Engineering, 2012)
Compact Models and Measurement Techniques for High-Speed Interconnects provides detailed analysis of issues related to high-speed interconnects from the perspective of modeling approaches and measurement techniques. Particular focus is laid on the unified approach (variational method combined with the transverse transmission line technique) to develop efficient compact models for planar interconnects. This book will give a qualitative summary of the various reported modeling techniques and approaches and will help researchers and graduate students with deeper insights into interconnect models in particular and interconnect in general. Time domain and frequency domain measurement techniques and simulation methodology are also explained in this book.